The risks of long-term re-injection in supercritical geothermal systems - Francesco Parisio (Nature Portfolio, 2019)
Can we pump water into deep active volcanic areas? Here, the authors model the effect of water circulation into supercritical geothermal systems and show that the effect of rock cooling dominates the seismicity increase over the pore pressure changes.